The Effects of Women on the Board on the Firm Performance of Thai Listed Companies - PETPAIROTE, Wannuda; CHANCHARAT, Nongnit (Journal of Advanced Research in Law and Economics; Vol 6 No 1 (2015): JARLE Volume VI Issue 1(11) Summer 2015, 2016)
This study examines the relationships between women on the board and the firm performance of the listed companies on the Stock Exchange of Thailand (SET). We employ observed data on SET Index firms from 7 industries (338 companies) in 2013. For our study of the associations between gender diversity on the board and firm performance, the estimations were conducted with a two- stage least- squares technique, using return on assets (ROA) as the well-known performance measurement technique. The results were significant for relationships between gender diversity and firm performance. The industry group, that is, Agro and Food, Technology, Services and Consumer Products, and so on, was also related to firm performance in Thai listed companies. This study contributes to our nascent understanding of the relationships between women on the board and the firm performance of Thai listed companies using multiple variants of gender diversity on the board. These experimental results are consistent with the corporate governance principles for listed companies on the SET from 2012, which focus on the gender diversity of the board. The study helps to reinforce these values in the corporate governance of the country via the relationships found with gender diversity, which affect firm performance across industries and in some specific industries.
Keywords: Corporate Governance, firm performance, gender diversity, women on board